2013
DOI: 10.3109/01942638.2013.794187
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Challenges of Collaborative Goal Setting with Children and Their Families

Abstract: Collaborative goal setting between clinicians and clients/families is considered a fundamental component of the pediatric rehabilitation process. However, truly client-centered goal setting is not without its challenges. The purpose of this paper is to highlight theoretical concepts relevant to rehabilitation goal setting, review clinical studies directly evaluating relationships between goal setting and pediatric rehabilitation outcomes, and provide recommendations to facilitate collaborative goal processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 30 publications
(45 reference statements)
5
70
0
Order By: Relevance
“…Finally, given the need for professional education in relation to collaboration and working with families identified in recent commentaries (e.g. Brewer et al, 2014) the findings can inform and pre-and postgraduation education in relation to working with families and children with DS.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, given the need for professional education in relation to collaboration and working with families identified in recent commentaries (e.g. Brewer et al, 2014) the findings can inform and pre-and postgraduation education in relation to working with families and children with DS.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Contemporary authors are advocating for the need for continuing professional development post graduation on collaborative goal setting and facilitating a collaborative process (e.g. Brewer et al, 2014).…”
Section: Collaboration With Therapist: Group Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novak, Cusick, and Lannin (2009) concluded that the use of occupational therapy home programs leads to observable gains in function and quality of movement. It is recommended that therapy should focus on the expectations of parents (Cohn, Kramer, Schub, & May-Benson, 2014) and that family-focused intervention, with collaborative goal setting, will result in improved outcomes for families (Brewer, Pollock, & Wright, 2014). Foster, Dunn, and Lawson (2013) and Graham, Rodger, and Ziviani (2009) mutually advocate for a parent coaching intervention model instead of direct child-focused intervention.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Within the context of UL intervention for children with CP, clinicians work within a framework of family-centred (King & Chiarello, 2014), goal-focussed (Brewer, Pollock, & Wright, 2014), functionally-oriented (Law & Darrah, 2014), and activity-based practice aimed at promoting the development of skills and mastery of tasks required for successful occupational performance, participation and engagement. Individualised goals typically focus on developing skills for increased independence in the areas of self-care, productivity, and leisure.…”
Section: Occupational Performance and Mastery Motivation: A Conceptuamentioning
confidence: 99%